The significance of knowledge and wisdom in Imam Maturidi's work “Kitabut Tawheed” (Eurasian Journal of Religious Studies, 2024)
Abu Mansur al-Maturidi lived during the Samani rule in Maurannahr, a period when the Abbasid caliphate was weakened and various religious beliefs, ideologies, and currents emerged. This period was marked by intensified attacks on the foundations of Islam from both internal and external sources. Abu Mansur al-Maturidi wrote works during a time when he studied religious currents, as well as various ideological and philosophical opinions that opposed the Islamic faith. He provided answers to these opposing views by accurately explaining the main religious beliefs of Islam, thus contributing to the formation of correct beliefs. The works of Abu Mansur al-Maturidi have recently gained significant attention in Kazakhstan. The findings related to faith in his works are significant for addressing current religious issues in society. Maturidi's "Kitabut Tawheed" analyses sensitive issues of Islam in a rational manner and defines its necessity in human life. The concept of knowledge and wisdom, in particular, influences the use of the human mind and understanding of the secret and purpose of God in creating creation, thereby achieving true knowledge. However, this topic has not been sufficiently studied. Key words: Maturidi, Knowledge, Wisdom, Justice, Creation, Attributes of God